Developing skills for employability with German Partners : 8 success stories from Turkey - Niediek, Silvia [Verfasser] (Bundesinstitut für Berufsbildung, 2014)
Each of the 'Developing Skills for Employability with German Partners' brochures presents eight vocational education and training success stories of German and international partners in various countries and regions. This brochure presents eight success stories of skill development realised in a joint effort by partners from Germany and Turkey. With its wide range of training offers and its strong emphasis on employability, 'Training - Made in Germany' has the potential to successfully contribute to the design process of the training system in Turkey via Turkish-German cooperation projects." (BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; I 1.4 Berufsbildungsprojekte/Entwicklungsprojekte; I 2.3.4 Asien; Berufsbildung; Internationale Zusammenarbeit; Bundesrepublik Deutschland; Türkei